PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rustam Effendi; Amrillah Azrin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
This study aims to determine whether or not the influence of Leverage (DAR) and Liquidity (CR) on Profitability (ROA) on Insurance companies listed on the Indonesia Stock Exchange during 2014 - 2018. In this study using secondary data, and the sampling method using purposive random sampling technique. The analytical method used is descriptive statistical analysis and inferential statistical analysis that is normality test, multiple linear regression analysis, and analysis of the coefficient of determination (R2). Hypothesis testing uses multiple linear regression analysis method with the help of SPSS version 25. The test results show that the first hypothesis Leverage (DAR) and Liquidity (CR) variables together (simultaneously) have a positive and significant effect on profitability (ROA) with a level of sig. F (0.009) <α (0.05). The second hypothesis (H2) Leverage variable (DAR) effects the profitability (ROA) which is shown to have a significant value of 0.011 <α 0.05. And The third hypothesis (H3) variable Liquidity (CR) has no effect on profitability (ROA) which is shown to have a significant value of 0.233> α 0.05. Keywords: Leverage (DAR), Liquidity (CR), Profitability (ROA)